ENDAPAN MERKURI (Hg) DI MUARA SUNGAI KIMA DAN TALAWAAN DARI KEGIATAN PERTAMBANGAN EMAS RAKYAT DI KABUPATEN MINAHASA UTARA - Markus T. Lasut (EKOTON, 2014)
Mercury (Hg) discharge through the artisanal gold mining activities is one of the environmental concerns due to its emission that may follows natural methylation of mercury to result environmental contamination with an impact in human health. To assess Hg deposit from such activities, sampling was carried out in a watershed area of Talawaan, North Minahasa Regency, where that type of mining are widely occurred. The sampling was focused at the river mouth of Kima and Talawaan inside the watershed. Moisture concent (MC) and total mercury (THg) on dry weight basis were measured in the sampled sediments. The results show that the MC of the samples in both rivers varied based on their sampling points; the average was 0.30 (30%) in Kima and 0.25 (25%) in Talawaan. The concentration of THg found in sediment of Kima river mouth was uniform from one point to the others. Conversely, it was forming a gradient in the Talawaan where the concentrations decreased at the points close to the beach. In Kima river mouth, the lowest and the highest THg concentrations were found at Point B and A, respectively; while its average concentration was 0.871 mg/kg. In Talawaan river mouth, the lowest and the highest concentration of THg were found at Point B and A, respectively. The average concentration of THg in this area was 0.383 mgkg. Comparing the results within the areas, the concentration of THg found at Talawaan river mouth was higher than Kima.